Mengucapkan Salam Dalam Pembentukan Akhlakul Karimah di Sekolah - Susrianingsih, (Al-Fikru: Jurnal Ilmiah, 2021)
Islamic teachings strongly encourage praying for one another and among the words that contain prayers are greetings. In summary assalamu'alaikum means to convey a message of peace, respect and prayer. Assalamu'alaikum warahmatullahi wabarakatuh means "may salvation, blessings and compassion (mercy) from Allah be with you / you". The Koran asserts, besides prayer, greetings are moral honors are: "The will of the human soul that gives rise to actions easily due to habits, without requiring consideration of the mind first. Akhlakul karimah in human life occupies an important place, as individuals and communities. If the character is good, it will be able to raise the status of a high degree and noble for himself, but if the character is damaged, then the low degree. Good character always makes someone feel safe and calm.